Paraoxonase-1 and Other HDL Accessory Proteins in Neurological Diseases - Judit Marsillach; Carlo Cervellati (MDPI AG, 2021)
The burden of neurological diseases continues to increase as they still are the leading cause of disability and the second-leading cause of death worldwide [...]